The Relationship between Respiratory Infections and Healthy Homes in Children Under Five, Indonesia 2013 - Hidayangsih, Puti Sari; Tjandrarini, Dwi Hapsari; Nainggolan, Olwin; Sukoco, Noor Edi Widya (Media Penelitian dan Pengembangan Kesehatan, 2017)
Â Environment plays a very important role in the spread of disease, especially in children under five. Healthy homes are believed to help reduce the prevalence of disease, especially acute respiratory infections (ARI) in infants. This article describes the relationship between healthy home and ARI in children under five. The analysis used the data of Basic Health Research (Riskesdas) 2013 and Potential Villages (PODES) 2014, in 33 provinces of Indonesia. The sample is 59,175 children under five, distinguished to have been diagnosed with or without ARI and with or without staying at healthy home. Healthy home indicators are prepared in accordance with the Healthy Home Technical Guidelines published by the Ministry of Health. There are 15 variables that make up 3 groups of components of healthy homes. The criteria assessment uses value and weight according to the guidelines. There are 2 component variables that could not be included in the composite healthy home due to data limitations, which are the behaviour of cleaning houses and toileting children. Data analysis using logistic regression. The proportion of healthy homes in Indonesia is still low. A total of 23.2% (n = 13,744) of households with under-fives children were declared as healthy homes, and 26% (n = 15,364) infants were diagnosed with ARI. Based on geographical location, Sumatera is the highest percentage of households with children under five who meet the criteria of healthy homes. A risk difference was found to be 1.13 times greater for children under five with ARI in households exposed to indoor air pollution in both healthy and nonhealthy homes. Air pollution in the home affects the incidence of ARI in infants. Regulation of the use of cooking fuel and friendly home lighting source is necessary.AbstrakLingkungan berperan sangat penting dalam penyebaran penyakit, terutama pada balita. Rumah sehat diyakini dapat membantu menurunkan prevalensi penyakit, terutama infeksi saluran pernafasan akut (ISPA) pada balita. Artikel ini memaparkan hubungan antara rumah sehat dan ISPA pada balita. Analisis menggunakan data Riset Kesehatan Dasar (Riskesdas) 2013 dan Potensi Desa (PODES) 2014, di 33 provinsi di Indonesia. Sampel adalah balita dengan jumlah 59.175 orang, dibedakan menjadi pernah didiagnosis ISPA atau tidak dan tinggal di rumah yang dikategorikan sehat atau tidak. Indikator rumah sehat disusun sesuai dengan Pedoman Teknis Penilaian Rumah Sehat yang dikeluarkan oleh Kementerian Kesehatan Dirjen P2M & PL dan Kepmenkes No. 829. Terdapat 15 variabel yang membentuk 3 kelompok komponen penyusun rumah sehat. Penilaian kriteria rumah sehat menggunakan nilai dan bobot sesuai pedoman. Terdapat 2 variabel komponen yang tidak dapat dimasukkan dalam komposit rumah sehat yaitu perilaku membersihkan lantai dan membuang kotoran anak ke toilet akibat keterbatasan data. Analisis data menggunakan regresi logistik. Proporsi rumah sehat di Indonesia masih rendah. Sebanyak 23,2% (n = 13.744) rumah tangga dengan balita dinyatakan sebagai rumah sehat, dan 26% (n = 15.364) balita didiagnosis ISPA. Ditinjau dari letak geografis, kawasan di pulau Sumatera merupakan yang tertinggi untuk persentase rumah tangga dengan balita yang memenuhi kriteria rumah sehat. Ditemukan perbedaan risiko sebesar 1,13 kali lebih besar balita menderita ISPA pada rumah tangga yang terpapar pencemaran udara dalam rumah baik pada rumah sehat maupun bukan rumah sehat. Pencemaran udara dalam rumah mempengaruhi kejadian ISPA pada balita. Diperlukan pengaturan penggunaan bahan bakar memasak dan sumber penerangan dalam rumah yang ramah lingkungan.